Pedagogical Insight of University Students into ChatGPT Use in Academic Writing - Untari, Maulidya; Trisanti, Novia (Journal of English Language and Education, 2026)
Artificial intelligence tools such as ChatGPT are increasingly integrated into EFL academic writing; however, empirical evidence regarding students’ perceptions, challenges, and ethical considerations remains limited. This study examines EFL university students’ perceptions of using ChatGPT in academic writing, focusing on perceived usefulness, challenges, and ethical awareness. Employing a case study design, data were collected through close-ended and open-ended questionnaires administered to EFL students. The findings indicate that students perceive ChatGPT as supportive for idea generation, grammatical accuracy, text organization, and time efficiency. Nevertheless, challenges related to the accuracy and reliability of AI-generated information were identified, highlighting the need for critical evaluation. In addition, students reported agreement with ethical considerations, particularly regarding plagiarism awareness and the view that ChatGPT should function as a supplementary tool rather than a primary source. Overall, the findings suggest that ChatGPT can support EFL academic writing when used critically and ethically.